The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1055/s-0033-1343356
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism after Traumatic Brain Injury

Abstract: No standard exists for venous thromboembolism (VTE) prophylaxis after traumatic brain injury (TBI). Caregivers agree that there is an early time point after injury in which the chances of spontaneous injury progression are high and the risks of prophylactic anticoagulation are excessive, and that these injuries eventually stabilize to the point that anticoagulation may be safely started. Translating this consensus into an application that can inform bedside decision making has not occurred. National groups hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Although the use of chemical VTE prophylaxis in patients with head injuries appears to be safe, adoption is slow and prospective trials are lacking. 16,17 Limitations Limitations of our study are related to the retrospective nature and lack of controlled protocol for chemical VTE initiation at our centre. While patients were similar in age, sex and injury scores, there was a significant differ ence in the percentage of highgrade splenic injuries, which could be a confounding factor and may highlight a reluctance to initiate chemical VTE prophylaxis in this particular subset of patients, leading to a selection bias that was unlikely to be overcome by using a larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of chemical VTE prophylaxis in patients with head injuries appears to be safe, adoption is slow and prospective trials are lacking. 16,17 Limitations Limitations of our study are related to the retrospective nature and lack of controlled protocol for chemical VTE initiation at our centre. While patients were similar in age, sex and injury scores, there was a significant differ ence in the percentage of highgrade splenic injuries, which could be a confounding factor and may highlight a reluctance to initiate chemical VTE prophylaxis in this particular subset of patients, leading to a selection bias that was unlikely to be overcome by using a larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Traumatic brain injury (TBI) patients treated in the intensive care unit (ICU) appear at high risk for venous thromboembolism (VTE), such as deep venous thrombosis (DVT) of the legs and pulmonary embolism (PE) [1][2][3]. Moreover, the occurrence of massive PE is a known cause of late death in trauma patients, and the risk is increased in patients with DVT [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In 2012, we published a study of 245 patients with at least two CT scans of the head who had been classified and followed per this original iteration of the Parkland Protocol between February 2010 and March 2011. 3 In that study, we found that spontaneous progression of hemorrhage occurred in 25% of subjects in the low-risk arm (n = 136), 43% of moderate-risk subjects (n = 42), and 64% of high-risk subjects (n = 67).…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of this spectrum of risk, we have constructed and promulgated a theoretical treatment algorithm for VTE prophylaxis after TBI, which we are calling the ''Parkland Protocol.'' 4,5 Based on a modification of injury patterns initially put forth by Berne and Norwood, 6-8 our original protocol and its subsequent iterations classify TBI patients as low, moderate, or high risk for spontaneous progression of their intracranial hemorrhage (ICH) pattern and tailor a VTE prophylaxis regimen to each arm (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%